Cenário preditivo para ocorrência de supressão na bacia do Alto Paranapanema para o ano de 2030 a partir da caracterização de variáveis biofísicas e antrópicas - Lima, Larissa Santana (Universidade Federal de São Carlos, 2025)
Brazilian development has been based on the exploitation and destruction of native vegetation, intensifying from the 1970s onward with urban, agricultural, and industrial expansion. The suppression of native vegetation, especially in tropical forests, leads to changes in the water cycle, increased carbon emissions, biodiversity loss, worsening climate change, among other impacts. The Atlantic Forest, which extends along most of the Brazilian coast, has suffered significant degradation, with only 12% of its original cover remaining. The Cerrado was exploited later; however, it has faced intense deterioration, with few protected areas. Both biomes are considered global biodiversity hotspots due to their rich biodiversity being under severe threat. Suppression has resulted in drastic fragmentation and biodiversity reduction, which is particularly notable in the Alto Paranapanema Basin, where the Atlantic Forest meets the Cerrado. Suppression can occur for different reasons, such as wildfires, clear-cutting for commercial purposes, or natural causes, including practices authorized by environmental licensing and laws. In this context, the study aimed to model a simulated suppression map for the year 2030 in the Alto Paranapanema Basin. The transition to the Mosaic of Uses showed the highest simulated transition percentage between 2020 and 2030, with a transition rate of 1.59%, followed by conversion to agriculture at 1.08%, while the transition to non-vegetated areas, which includes urban areas, showed a simulated transition of 0.02% for the same period. These results, combined with the variables used, indicate that the trend of expansion toward these activities continues, especially associated with resources, accessibility, and infrastructure.
Predictive scenario for suppression occurrence in the Alto Paranapanema Basin for the year 2030 based on the characterization of biophysical and anthropic variables
Keywords: Supressão Vegetal; Cenários Preditivos; Dinamica Ego; Modelagem Ambiental; Uso e Cobertura da Terra; Vegetation Suppression; Predictive Scenarios; Environmental Modeling; Land Use and Land Cover; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::MANEJO FLORESTAL::POLITICA E LEGISLACAO FLORESTAL